1997
DOI: 10.1164/ajrccm.155.3.9117012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment with oral corticosteroids on asthma symptoms and airway inflammation.

Abstract: To improve understanding of the mechanisms of action of oral corticosteroids in asthma, we have conducted a double-blind, placebo-controlled study with prednisolone (20 mg for 2 wk followed by 10 mg for 4 wk) or placebo in 14 and 13 atopic corticosteroid-naive asthmatic subjects, respectively. Before and after treatment subjects underwent bronchoscopy with bronchoalveolar lavage (BAL) and bronchial biopsy. Treatment with prednisolone, but not placebo, significantly reduced asthma symptoms (from mean +/- SEM to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 0 publications
10
50
2
2
Order By: Relevance
“…Recently, it was reported that CD4 cell numbers were decreased in bronchial biopsies from asthmatics treated with oral prednisolone. 27 The authors speculated that CD4 cells may play an important part in asthmatic inflammation, and we believe our data suggest an analogous role for CD4 cells in BPD.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, it was reported that CD4 cell numbers were decreased in bronchial biopsies from asthmatics treated with oral prednisolone. 27 The authors speculated that CD4 cells may play an important part in asthmatic inflammation, and we believe our data suggest an analogous role for CD4 cells in BPD.…”
Section: Discussionsupporting
confidence: 64%
“…Both cytokines are partly dependent on cell-cell interaction involving the costimulatory molecule CD28 and its ligand B7. The observed inhibitory effect of dexamethasone on the production of IL-16 and RANTES and on the chemotactic activity is in keeping with the ability of corticosteroids to reduce the numbers of CD4 ϩ T cells in the airways mucosa (25). Finally, in showing a significant inhibitory effect of the proteasome inhibitor PSI on IL-16 generation and T cell chemotactic activity, we have shown a role for NF-B in partially regulating these components of the inflammatory response in asthma.…”
Section: Discussionsupporting
confidence: 82%
“…Throughout the past several years the compliant use of inhaled steroids has proven to be important in the control of atopic asthma. [7][8][9][10][11] However, because of continued development of steroid resistance and side effects that have been attributed to long-term steroid use, other alternatives have been explored. In particular, an attractive set of targets is the chemokine family members and their receptors that are responsible for the recruitment of particular subsets of leukocytes to the inflamed lung.…”
mentioning
confidence: 99%